Written Language Outcomes of Deaf Elementary Students Engaged in Authentic Writing. (8th February 2020) - Wolbers, Kimberly A; Dostal, Hannah M; Cihak, David; Holcomb, Leala
Abstract: This study explores the impact of Strategic and Interactive Writing Instruction (SIWI) on six students' written language skills through the application of a multiple-baseline probe single case design with embedded condition. This was part of a larger Institute of Education Sciences (IES)-funded project focused on the development and feasibility of implementation of SIWI. For the majority of skills analyzed, there were improvements in the mean level of performance with the implementation of SIWI, as well as more consistent responding and positive trends in the data. The study also revealed that teachers are in need of additional tools to aid the systematic identification and tracking of syntax skills in children's written language development, and to distinguish these from other writing skills such as conventions or handwriting.